ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA MELALUI PENDEKATAN SAINTIFIK PADA MATERI BENTUK ALJABAR KELAS VII DI SMP PATARUMAN - Mira Fauziyah Hamdani; Anik Yuliani; M. Afrilianto (IKIP Siliwangi, 2023)
This paper aims to describe students' mathematical critical thinking skills through a scientific approach to the subject matter of algebraic forms in grade VII SMP Pataruman. This research uses classroom action research method. The subjects of this study were 25 students of class VII-A of SMP Pataruman Cihampelas in the odd semester of the 2021/2022 academic year. This research was conducted through 2 cycles, each of which was carried out by following the procedures, namely planning, implementing actions, observing, and reflecting. The first cycle was carried out by distance learning (online), while the second cycle was carried out face-to-face (offline). The data collection instruments used in this study were test instruments in the form of pretest and posttest, learning independence questionnaires, and observation sheets for teacher and student activities. The results showed that there was an increase in students' mathematical critical thinking skills in grades VII-A of SMP Pataruman on the subject matter of algebra by applying a scientific approach.